The Influence of the Use National Traffic Management Center (NTMC) Technology at the National Police Traffic Corps Contact Center in Handling Traffic Accidents - Sinurat, Susi Nurdecta Secondgirls; Basir, Basir; Setyabudi, Chairul Muriman (International Journal Labs, 2023)
This research aims to analyze the influence of the use of National Traffic Management Center (NTMC) technology at the National Police Traffic Corps contact center in handling traffic accidents. The government, through Korlantas Polri, established the National Traffic Management Center (NTMC) to realize safe, secure, orderly, and integrated traffic and road transportation services. The service provided is in the form of the NTMC Contact Center application which was developed in 2017 to complement the call center and SMS center services that have been available since 2014. The ease of use of technology and the provision of quality services will have an impact on community satisfaction. The purpose of this research is to analyze the influence of acceptance of the use of technology, the influence of service quality on the NTMC Contact Center application for the National Police Traffic Corps, and the simultaneous influence of acceptance of the use of technology and quality of service on the NTMC Contact Center application for the National Police Traffic Corps on the level of public satisfaction in handling traffic violations and accidents. Theoretical concepts in the Technology Acceptance Model, User Acceptance, and Community Satisfaction are used to analyze the acceptance of technology use and service quality on community satisfaction in the NTMC Contact Center application for the National Police Traffic Corps. The research method used in this research is quantitative explanatory research with a population of 10,000 people who downloaded the NTMC Contact Center Polri application on Google Playstore. From the total population, a sample of 100 people can be obtained using the Slovin formula. The sampling technique used was the snowball sampling technique. The results of the research show that there is a positive and significant influence of acceptance of the use of technology, influence of service quality, and a simultaneous influence of acceptance of the use of technology and service quality in the NTMC Contact Center application on the level of public satisfaction in handling traffic violations and accidents.